2010
DOI: 10.1111/j.1365-3091.2009.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential and climatic framework of the growth and demise of a carbonate platform: implications for the peritidal cycles (Late Jurassic, North-eastern France)

Abstract: International audienceThe Middle Oxfordian of the eastern Paris Basin constitutes a remarkable example of the growth and demise of a carbonate platform. Fischer plots, sedimentary and diagenetic features allow the identification of four depositional cycles (S5 to S8) in the Transversarium Zone; they are inserted in a lower frequency cycle of increased/decreased accommodation space (SoIII). The long-term period of accommodation creation occurred during the older S5 and S6 cycles, the maximum accommodation zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…In the Calcaires de Dainville Member, exposure surfaces are closely stacked. This formation was deposited during a period of low accommodation, and the occurrence of rootlets below surfaces of subaerial exposure suggests that exposure was more prolonged than in the lower part of the middle Oxfordian (Carpentier et al 2010). In the late Oxfordian, surfaces also show indications of prolonged subaerial exposure such as karstification and vadose cements (Oolithe de Saucourt Member).…”
Section: Geographical and Geological Frameworkmentioning
confidence: 98%
See 1 more Smart Citation
“…In the Calcaires de Dainville Member, exposure surfaces are closely stacked. This formation was deposited during a period of low accommodation, and the occurrence of rootlets below surfaces of subaerial exposure suggests that exposure was more prolonged than in the lower part of the middle Oxfordian (Carpentier et al 2010). In the late Oxfordian, surfaces also show indications of prolonged subaerial exposure such as karstification and vadose cements (Oolithe de Saucourt Member).…”
Section: Geographical and Geological Frameworkmentioning
confidence: 98%
“…During the middle Oxfordian, a shallow carbonate platform developed in the eastern Paris Basin (Ziegler 1990;Thierry 2000;Ferry et al 2007;Carpentier et al 2010) located between 30 and 35u N (Kiessling et al 1999). Southward, the shallow, clay-free carbonate facies graded laterally into argillaceous carbonates of the basinal environment near the Marne Valley (Fig.…”
Section: Geographical and Geological Frameworkmentioning
confidence: 99%
“…Between the Paris Basin to the northwest and the Ligurian segment of the Mesozoic Tethys to the southeast, extensive shallow carbonate areas constituted the Jura, Lorraine and Swabian platforms (Reinhold 1998;Colombié and Strasser 2005;Carpentier et al 2010). The growth and demise of these carbonate platforms occurred in various climatic, eustatic and tectonic contexts (Pittet and Strasser 1998;Pittet et al 2000;Jank et al 2006a;Carpentier et al 2006Carpentier et al , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Late Jurassic carbo nates recorded orbital (Milankovitch) cycles that were responsible for low-amplitude sea-level changes (Strasser 2007;Strasser et al 1999Strasser et al , 2012. Other factors, apart from sea-level variations, that can affect carbonate production are siliciclastic and nutrient input (Mutti and Hallock 2003;Carpentier et al 2010). The Late Jurassic generally is thought to have had an equable global climate and warm temperatures (Frakes et al 1992;Hallam et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore the combination of autogenic/autocyclic and allogenic/allocyclic processes that is responsible for sediment deposition and the formation of the final sedimentary record. Many case studies have already shown and discussed the coexistence of autocyclic and allocyclic processes, for example: Sami and James (1994) in the Proterozoic of northwest Canada; Jiang et al (2003) in the Proterozoic of the Lesser Himalaya; Adams and Grotzinger (1996) in the Middle Cambrian of California; Cowan and James (1993) in the Late Cambrian of Newfoundland; Smith and Read (2001) in the Mississippian of Illinois; Yang et al (1998) in the Late Pennsylvanian and Early Permian of Texas; Bádenas et al (2010) in the Sinemurian of Spain; Carpentier et al (2010) in the Oxfordian of France; Sattler et al (2005) in the Barremian and Aptian of Oman; Lehmann et al (1998) in the Barremian to Albian of northeastern Mexico; Rankey (2002) in the Holocene of the Bahamas.…”
Section: Autocyclic Processesmentioning
confidence: 99%